Pelaksanaan Bimbingan Klasikal yang Berpihak pada Peserta Didik: Tinjauan Terhadap Metode, Praktik dan Tantangan - Sofyati Halmahera, Amelia Dhamara; Anisa Dwi Pratanti; Dhika Chelvian Satya Benardy; Sholikhul Huda (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
This study aims to explore various methods used in the implementation of classical guidance services in the era of the independent curriculum. Through a literature review research method, we examined a number of research articles discussing practices and challenges in the implementation of classical guidance services. The research findings indicate that various methods such as Project Based Learning (PJBL), Problem Based Learning (PBL), Cooperative Learning, Experiential Learning, and Discovery Learning have been proven effective in enhancing various aspects of students' development. The research also identifies some challenges in the implementation of classical guidance services, including lack of communication between guidance counselors and homeroom teachers, resource limitations, and lack of understanding or confidence from guidance counselors regarding the methods to be applied. Thus, this research provides insights into various methods that can be used in the implementation of classical guidance services as well as the challenges that may be encountered in the implementation process. It is expected to contribute to the development of guidance and counseling practices in schools.